PERBEDAAN TARIF ASUHAN KEHAMILAN DAN PERSALINAN ANTARA PESERTA BPJS KESEHATAN DAN NON-BPJS KESEHATAN - Astri Nurdiana; Ella Nurlailasari (UPT PPM Sekolah Tinggi Ilmu Kesehatan Al Irsyad Al Islamiyyah Cilacap, 2020)
Enforcement of national health insurance organized through Badan Penyelenggara Jaminan Kesehatan experiences various polemics, one of which relates to financing for midwifery care listed in Permenkes No. 52 of 2016 concerning health service fare standards in the health insurance program, whether the standard tariff can cover the needs of services provided by midwives in rural or urban areas or not. The result found that there is no difference in antenatal care tariff between urban and rural areas (p>0.05), while there are differences in antenatal care tariff between urban tariff and UHC tariff standard (p<0.05), additionally there are significant different between both normal and childbirth with emergency condition tariff of UHC and urban and rural areas tariff (p< 0.05)